The Impact of Social Media Platforms on Communication Development Between Schools and Parents: (A Qualitative Study of Teachers and Parents) - Abdulelah H. Alshehri (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
The use of social media and mobile communication technologies has revolutionised communication in education, especially in improving school-family engagement. This study aims to examine the role of social media platforms in enhancing the process of communication and knowledge sharing between teachers and parents in Angal Al-Safwa School, particularly the WhatsApp platform. The study examines the impact of digital platforms on the enhancement of information sharing, parental involvement, and home/ school partnerships. For an in-depth understanding of the experiences and perceptions of the participants, a qualitative research design was used. The data was gathered by means of semi-structured interviews with 30 respondents, comprising 16 teachers and 14 parents from the selected school. The interviews centred on the participants’ perspectives on the effectiveness of social media to facilitate communication, to resolve issues in the traditional school system, and to improve knowledge management practices. Interviews were conducted in Arabic and then transcribed and translated into English, and then analysed based on thematic content analysis to find the common patterns and themes. The results are anticipated to show that social media can help to communicate more quickly, enable greater involvement from parents and provide efficient knowledge transfer between schools and parents. The study helps in filling in the existing stream of research on digital communication in education and offers insights for educators who want to improve parent–teacher relationships using technology.